(untitled) (Economics and region, 2022)
The article examines the peculiarities of the use of social marketing tools by local governments. Aspects of the use of marketing in public administration and its specifics are considered. It is determined that territorial marketing is a type of marketing in public administration and is related to ensuring the interests of the territory and operates as a relevant service of public administration and local government. It was found that social marketing is the use of marketing tools and means to carry out socially significant transformations and strengthen non-profit organizations. Social marketing has been found to address three issues: belief, social practice, and social product. The tasks of local self-government are the implementation of social programs, and to take into account the interests of the public, a dialogue between local authorities and the population is necessary. The practice of local self-government development shows that the successful solution of issues of local importance depends on such factors as: natural resource provision, economic and financial support. At the same time, financial security is the most important. To implement the principles of local self-government and effective resolution of issues, it is advisable to use the tools of social marketing. The peculiarities of social marketing planning for the implementation of social programs by local governments, as well as identifying possible ways to use tools in their promotion. The place and role of social advertising in society is determined and a number of its functions are highlighted. It was found that public relations is an important tool of social marketing in the system of local government and identified the main areas of PR activity, namely the use of various manipulative technologies. As a result of the study, the impact of social marketing measures on the implementation of public activities by local governments and identified that the use of marketing techniques in their activities will significantly improve its effectiveness.